In the liminal realm: Qatar's world cup struggle between tradition, modernity, and human rights - Al-Thani, Mohammed (Frontiers in Sports and Active Living, 2025)
This paper examines Qatar's 2022 World Cup through the lens of liminality, presenting the intricate interplay between tradition, modernity, and human rights. By introducing liminality as an analytical tool, the paper explores how Qatar navigates traditional norms amidst global scrutiny, particularly concerning human rights issues such as migrant labour practices and cultural contestations around human rights. Employing liminality as a conceptual framework, this analysis offers a nuanced understanding of Qatar's endeavour to balance cultural authenticity with international expectations. I reveal why Qatar utilised the transient phase to implement reforms to its social and legal systems, aligning with international human rights while ensuring changes were akin with its cultural identity. The paper highlights the transient nature of change during the liminal phase of sport mega-events, emphasising both the opportunities and challenges presented for changes in Qatar. The paper unpacks Qatar continued navigation in the global stage as an extension of the initial liminal phase, demonstrating its engagements with processes of change and adaptation. The World Cup is a prime example that exposes the dual nature of sport mega events, serving as a springboard for social change, while also revealing underlying cultural and structural tensions. I conclude that Qatar utilised this liminal phase as a rite of passage, enabling the nation to traverse the terrain of modernity while testing the permeability of its cultural boundaries.